Integration of Local Wisdom and Islamic Values as a Foundation for the Strengthening of Character Education in the Modern Era - Erwin, Erwin; Sabri, Ahmad; Hidayati, Hidayati; Alindra, Afridha Laily (Fitrah: Journal of Islamic Education, 2025)
Globalization and technological developments have posed significant challenges to students’ character education, including weakened morality, rising individualism, diminished appreciation of cultural values, and reduced sensitivity to religious teachings. This study aims to analyze the implementation of integrating Minangkabau local wisdom and Islamic values in character education at SMAN 1 West Sumatra, as well as the strategies employed by the school to optimize this integration. The study uses a qualitative case study approach, involving in-depth interviews with school leaders, teachers, and students, participatory observations, and analysis of school documents and visual archives. Data were thematically analyzed using the interactive model of Miles, Huberman, and Saldaña, with triangulation to ensure validity. The results show that character internalization occurs holistically through habituation, teacher role modeling, school routines, religious and social activities, and community involvement. Values such as honesty, discipline, responsibility, and tolerance are internalized practically. Integrating Islamic values with the principle of Adat Basandi Syara’, Syara’ Basandi Kitabullah strengthens students’ religious and cultural identity while equipping them with moral, social, and reflective competencies relevant to modern challenges.